1998
DOI: 10.1037/0012-1649.34.4.731
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning about responsibilities and obligations in close relationships: A comparison across two cultures.

Abstract: The study compares sociomoral reasoning of children and adolescents in Iceland, longitudinally assessed at ages 7, 9, 12, and 15 years (N = 97), and in China, cross-sectionally assessed at corresponding ages (N = 350). Participants reasoned about choices, motives, and moral justifications of a protagonist in a sociomoral dilemma. The dilemma allows persons to focus on different concerns (e.g., promise keeping or close friendship vs. self-interest or altruism toward a 3rd person). Overall, Icelandic participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 15 publications
5
54
1
Order By: Relevance
“…Vice versa, the younger children focused more than the older children on the hedonistic gains achieved by the moral transgressions. These findings support the view that moral cognitions develop over time; morally less mature justifications decrease and justifications related to moral principles increase [Edelstein et al, 1990;Keller et al, 1998]. …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Vice versa, the younger children focused more than the older children on the hedonistic gains achieved by the moral transgressions. These findings support the view that moral cognitions develop over time; morally less mature justifications decrease and justifications related to moral principles increase [Edelstein et al, 1990;Keller et al, 1998]. …”
Section: Discussionsupporting
confidence: 77%
“…It thus seems important to include children's moral reasoning about their emotion attributions in analyzing moral antecedents of aggressive and prosocial behavior. This argument is particularly relevant to older children, because the diversity of justifications increases with age [Keller et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Popular writers on evolution often scoff at the absurdity of such a constraint (Low, 2000;Dawkins, 1976Dawkins, , 1982Ridley, 1993), despite the fact that the available empirical evidence is somewhat mixed. Keller et al (1998) have shown empirically that an odor-based signal explains large-scale cooperation in the red fire ant. In humans, experimental work suggests that people have some ability to distinguish cooperators from defectors (Frank et al, 1993;Brown and Moore, 2002), although other work says they cannot (Ockenfels and Selten, 2000;Ekman, 1992;Ekman and O'Sullivan, 1991;Henrich and Smith, in press).…”
Section: Green Beardsmentioning
confidence: 99%
“…The friend wants to show a new toy or CD to the protagonist but also wants to talk about something important. The new classmate just moved to the area and does not have friends yet (Keller, 2004;Keller, et al 1998). Participants were asked to reason about what the protagonist decided to do (practical decision) and what was the right thing to do in that situation (moral judgment).…”
Section: Culture and Moral Reasoningmentioning
confidence: 99%